New Developments in Electrochemical Sensors Based on Poly(3,4-ethylenedioxythiophene)-Modified Electrodes - Stelian Lupu (International Journal of Electrochemistry)
There is a growing demand for continuous, fast, selective, and sensitive monitoring of key analytes and parameters in the control of diseases and health monitoring, foods quality and safety, and quality of the environment. Sensors based on electrochemical transducers represent very promising tools in this context. Conducting polymers (CPs) have drawn considerable interest in recent years because of their potential applications in different fields such as in sensors, electrochemical displays, and in catalysis. Among the organic conducting polymers, poly(3,4-ethylenedioxythiophene) (PEDOT) and its derivatives have attracted particular interest due to their high stability and high conductivity. This paper summarizes mainly the recent developments in the use of PEDOT-based composite materials in electrochemical sensors.